Ustrojowe znaczenie konstytucyjnego ustanowienia stolicy w państwach członkowskich Unii Europejskiej - Grabowski, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The practice of placing in the constitution provisions relating to state symbols emblem, flag, anthem is satisfactory. Often accompanying such regulation standards is the task to indicate the center of which is the state capital. The desirability of such regulations is questionable, hence the question whether it is acommon practice. The analysis covers the EU Member States. It is ainhomogeneous group, which should be considered an advantage, because it allows to review the solutions. The aim is to answer the question whether in the EU countries there is awidespread practice of the constitutional establishment of the state capital, whether it is the dominant model, is it possible there are different solutions in this area, when such adjustments are redundant, whether such cases allow conclusions that can be applied in practice of Polish political system.
Keywords: symbole państwa; ustanowienie konstytucyjne; Unia Europejska